Prevalence of uncontrolled hypertension and associated factors among hypertensive patients attending medical outpatient clinic, Thika level 5 hospital, Kenya - Gladys, Magara Monyenye; Gachohi, John; Muriithi, Alex (International Journal Of Community Medicine And Public Health, 2021)
Background: Uncontrolled hypertension is a key risk factor for stroke and heart and kidney disease. A study was conducted to determine the factors associated with the prevalence of uncontrolled hypertension among hypertensive patients (study participants) attending a medical outpatient clinic, Thika level 5 Hospital (TL5H), Kenya. Methods: The study adopted a cross-sectional study design and a mixed-methods approach. While the quantitative arm sampled 394 study participants using systematic random sampling, purposive sampling selected 18 health care workers who served as key informant sand 35 study participants took part in focus group discussions in the qualitative arm. Uncontrolled hypertension was defined as systolic and or diastolic blood pressure ≥140 and or ≥90 in one or both previous and current readings during clinic visits. Quantitative data including socio-demographic, socioeconomic, and clinical characteristics of study subjects were collected using interviewer-administered questionnaires. Qualitative data were collected using guides and checklists. Data were analysed descriptively and inferentially using Pearson’s chi-square statistics, Fishers exact tests and regression modelling to determine associations between independent variables and uncontrolled hypertension using STATA 14. Qualitative data were organized thematically using NVIVO. Results: 48% of the study participants had uncontrolled hypertension at the time of the study. Univariable analyses returned level of education (p=0.017), source of financing for hypertensive drugs (p=0.011), BMI (p=0.005) as significant factors. Conclusions: The study recommends community health promotion activities to increase awareness of how to modify these significant factors to reduce hypertension.